A record of post-collisional transition: evidence from geochronology and geochemistry of Palaeozoic volcanic rocks in the eastern Junggar, Central Asia. Issue 10 (27th July 2017) - Luo, Ting; Liao, Qunan; Chen, Jiping; Hu, Chaobin; Wang, Fuming; Chen, Shuai; Wu, Weiwei; Tian, Jian; Fan, Guangming
ABSTRACT: Abundant clues about the post-collisional transition in the southwestern margin of the Central Asian Orogenic Belt (CAOB) have been recorded by the late Palaeozoic volcanic rocks in the eastern Junggar region. These volcanic rocks provide a better window for understanding the magmatic and tectonic transition processes. This paper reports detailed petrology, whole-rock and Sr–Nd–Pb isotope geochemistry, and in situ zircon U–Pb dating analyses of these volcanic rocks from this region. Systematic geochemical and geochronological studies show that three stages of magmatism were recorded in this area, including ca. 407 Ma and ca. 340 Ma medium-to-high-K calc-alkaline series and ca. 320 Ma alkaline and tholeiite series. The ca. 407 Ma volcanic rocks have calc-alkaline compositions, strong enrichment in large-ion lithophile elements (LILEs) and depletion in high-field strength elements (HFSEs), negative Nb anomalies, and light REE (rare earth element)-enriched patterns. The ca. 340 Ma volcanic rocks, which have similar calc-alkaline compositions and arc geochemical affinities but higher K content, have slightly lower Th/Yb and Ba/Nb values than typical island arc or continental margin volcanic suites. The compositions of the ca. 320 Ma volcanic rocks display a bimodal distribution; the ca. 320 Ma basaltic rocks are chemically similar to oceanic island basalt (OIB) but with slight depletion in Nb and Ta, wheres the acidic rocks show the features of A-type granite. The chemical compositions of these volcanic rocks indicate that the ca. 407 Ma magmatism was subduction related, while the ca. 340 Ma and ca. 320 Ma volcanic rocks were the product of post-collisional magmatism. This transition from ca. 407 Ma to ca. 320 Ma records slab subduction, slab break-off, and slab rollback and provides a plausible explanation for the complex spatial and temporal geochemical evolution of magmatism in eastern Junggar since the Devonian.